Landscape configuration of crops and hedgerows drives local syrphid fly abundance. Issue 2 (19th February 2014) - Haenke, Sebastian; Kovács‐Hostyánszki, Anikó; Fründ, Jochen; Batáry, Péter; Jauker, Birgit; Tscharntke, Teja; Holzschuh, Andrea; Osborne, Juliet
Summary Human‐dominated landscapes are characterized by a mosaic of natural and managed ecosystems, affecting arthropod communities on different spatial scales. Effective landscape management for functionally important organisms suffers from little understanding of organism spillover between semi‐natural habitats and adjacent crops, and of how it is affected by the surrounding landscape. We examined syrphid abundance (Diptera: Syrphidae) in three types of linear semi‐natural habitats, differing in connectedness to annual crops and forest [forest edges (n = 12), forest‐connected hedges (n = 11) and isolated hedges (n = 12)], as well as in the adjacent oilseed rape or winter wheat fields (i.e. altogether n = 70 sites in 35 landscapes). The landscape circles with 1 km radius around the study sites differed in the proportion of oilseed rape (ranging from 0% to 35% oilseed rape) enabling us to test landscape‐scale effects of oilseed rape. Aphidophagous syrphids were more abundant in forest‐connected hedgerows than in forest edges (with isolated hedges being intermediate), and more abundant in crop fields adjacent to hedgerows than adjacent to forest edges, indicating spillover from semi‐natural habitats to the adjacent crop fields. Aphidophagous syrphid abundance was higher in semi‐natural habitats adjacent to oilseed rape fields than adjacent to wheat fields if the proportion of oilseed rape in the landscape was low (indicating local concentration). Synthesis and applications. This study highlights the potential of hedgerows to enhance the abundances of beneficial syrphids and their spillover to adjacent crop fields, especially when they are connected with forests. We provide evidence that this local exchange is moderated by the extent of mass‐flowering crops in the surrounding landscapes due to local concentration. Therefore, measurements for the improvement in local biological functioning should be evaluated by simultaneously investigating local and regional aspects of crop configurations to allow for region‐specific management recommendations. Increasing the total amount of hedgerows in the agricultural matrix under moderate landscape‐scale proportions of mass‐flowering crops may serve best for the conservation of biodiversity and augmentation of important ecosystem services such as biological control and pollination in landscapes dominated by agricultural cultivations.